Availability and stability of soluble fluoride content in commercial fluoride dentifrices available in Uruguay - Anunzziatta Fager FABRUCCINI; Licet Loureiro ALVAREZ; Marisa MALTZ; Lina Naomi HASHIZUME (Faculdade São Leopoldo Mandic, 2020)
ABSTRACT Objective The aim of this study was to evaluate the availability and stability of soluble fluoride fraction in commercial fluoride toothpastes available in Uruguay. Methods Fourteen fluoride toothpastes from four different manufacturers were analyzed. Randomized and blinded analyses were performed in duplicate for each dentifrice at the time of purchase (fresh samples) and after 12 months of storage at room temperature (aged samples). Total fluoride and total soluble fluoride concentrations were measured using a fluoride specific electrode. Results Total fluoride concentrations in all of the products were lower than the F levels specified by the manufacturers. Total soluble fluoride fractions were lower than the total fluoride concentrations in fresh samples of five toothpastes and in aged samples of ten toothpastes (p < 0.05). Three toothpastes had insufficient and unstable total soluble fluoride fractions (< 60%) and five toothpastes had only unstable total soluble fluoride fractions (<1000 ppm) after 12 months. Conclusion Based on theresults of this study, it can be concluded that from fourteen Uruguayan commercial fluoride toothpastes analyzed in this study, three toothpastes have insufficient and unstable chemically active F fractions and five other toothpastes have the lack of stability which may compromise their efficacies. Review the guidelines on fluoride dentifrices in Uruguay is necessary, in order to ensure optimum benefit for population.